Assessment of fluoride in commonly used local and imported toothpastes in the Iranian market - Afsaneh Pakdaman; Behrouz Akbari-Adergani (Tehran University of Medical Sciences, 2018)
Background and Aims: The systemic and topical preventive effect of fluoride on tooth decay has been reported. The aim of the present study was to determine the fluoride level in imported and national fluoridated dentifrices in the Iranian market. Materials and Methods: Sampling was randomly performed from the main market centers and pharmacies in Tehran. The total fluoride (TF) and total soluble fluoride (TSF) concentrations were determined by ion specific electrode potentiometer method. The samples were coded and one trained researcher performed the analysis. Descriptive statistics as percentage and analytical statistics reported as independent t-test were reported. Results: In adults' toothpastes, the total fluoride ranged from 191 to 1601.9 ppm with the mean of 911.2 (SD=331.4) ppm. The total soluble fluoride ranged from 322.8 to 1518.8 ppm with the mean of 1021 (SD=279.8) ppm. In children's toothpaste total fluoride ranged from 236.3 to 1163.7 ppm and the total fluoride of 594 (SD=375). Total soluble fluoride in children's toothpaste ranged 655.6-1102.6 with the mean of 879.1 (SD=316.07). Analysis of the total fluoride (TF) and total soluble fluoride (TSF) showed that there was no significant difference between the local and imported toothpastes (P>0.05). Conclusion: The fluoride level of Iranian toothpaste was similar to that of the imported toothpastes, however there was variation in the level of fluoride in products.